Do Auditors Recognize the Potential Dark Side of Executives' Accounting Competence? - Albrecht, Anne; Mauldin, Elaine G.; Newton, Nathan J. (The Accounting Review, 2018)
ABSTRACT Practice and research recognize the importance of extensive knowledge of accounting and financial reporting experience for generating reliable financial statements. However, we consider the possibility that such knowledge and experience increase the likelihood of material misstatement when executives have incentives to misreport. We use executives' prior experience as an audit manager or partner as a measure of extensive accounting and financial reporting competence. We find that the interaction of this measure and compensation-based incentives increases the likelihood of misstatements. Further, auditors discount the audit fee premium associated with compensation-based incentives when executives have accounting competence. Together, our results suggest that a dark side of accounting competence emerges in the presence of certain incentives, but auditors view accounting competence favorably despite the heightened risk. In further analyses, we demonstrate that executives' aggressive attitude toward reporting exacerbates the effect of accounting competence and compensation-based incentives on misstatements, but not on audit fees. JEL Classifications: M41; M42. Data Availability: Data are available from public sources identified in the text.